Improving Students’ Learning Outcomes in Science through the Implementation of Problem-Based Instruction - Majenun Majenun (USN Kolaka, 2025)
Learning outcomes in science subjects are strongly influenced by the learning strategies implemented in the classroom. However, many students still experience difficulties in understanding scientific concepts due to passive learning environments and limited student engagement. This study aims to improve students’ learning outcomes in science through the implementation of the Problem-Based Instruction (PBI) model. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were students of Grade VII at SMP Negeri 27 Rarowatu Utara during the academic year 2024/2025. Data were collected through observation, learning achievement tests, and documentation. The collected data were analyzed using descriptive quantitative and qualitative techniques. The results indicated a significant improvement in students’ learning outcomes after the implementation of the Problem-Based Instruction model. In Cycle I, students’ learning achievement showed moderate improvement, while in Cycle II, students demonstrated higher mastery of the learning material and increased active participation during the learning process. These findings indicate that Problem-Based Instruction effectively enhances students’ understanding, engagement, and critical thinking skills in science learning. Therefore, it can be concluded that the implementation of Problem-Based Instruction contributes positively to improving students’ learning outcomes and creating a more meaningful and student-centered learning environment.